Pengaruh Kualitas Pelayanan Koperasi Dan Citra Koperasi Terhadap Kepuasan Nasabah Pada Koperasi Serba Usaha Mitra Karya Lubuk Pakam - Tuberta Ndruru; Martua Sitorus (Junal Ilmu Manajemen, 2018)
This study aims to determine the effect of cooperative service quality and cooperative image on customer satisfaction and to determine the dominant variable on customer decisions in using the services of KSU Mitra Karya Lubuk Pakam. The sample used in this study is employees of KSU Mitra Karya Lubuk Pakam, aged 17 years or older, can communicate well, and are able to provide good service to customer satisfaction. The number of samples is calculated using the formula according to Sugiyono and Slovin theory, so we get a total sample of 88 people. The results of this study use quantitative methods that show that the variables used, namely the quality of cooperative services (X1), cooperative image (X2), and customer satisfaction (X3), have a positive and significant effect on customer satisfaction in using the services of KSU Mitra Karya Lubuk Siram. The results of this study also show that the dominant variable influencing customer decisions in using the services of Mitra Lubuk Pakam KSU is the quality of cooperative services (X1), the image of cooperatives (X2), and customer satisfaction (X3).